The Drosophila Hox gene ultrabithorax acts in both muscles and motoneurons to orchestrate formation of specific neuromuscular connections - Hessinger, Christian; Technau, Gerhard; Rogulja-Ortmann, Ana (Development, 2017)
Hox genes are known to specify motoneuron pools in the developing vertebrate spinal cord and to control motoneuronal targeting in several species. However, the mechanisms controlling axial diversification of muscle innervation patterns are still largely unknown. We present data showing that the Drosophila Hox gene Ultrabithorax (Ubx) acts in the late embryo to establish target specificity of ventrally projecting RP motoneurons. In abdominal segments A2 to A7, RP motoneurons innervate the ventrolateral muscles VL1-4, with VL1 and VL2 being innervated in a Wnt4-dependent manner. In Ubx mutants, these motoneurons fail to make correct contacts with muscle VL1, a phenotype partially resembling that of the Wnt4 mutant. We show that Ubx regulates expression of Wnt4 in muscle VL2 and that it interacts with the Wnt4 response pathway in the respective motoneurons. Ubx thus orchestrates the interaction between two cell types, muscles and motoneurons, to regulate establishment of the ventrolateral neuromuscular network.
Published as accepted manuscript 2 December 2016 and published as research article online January 3, 2017
Gesehen am 13.06.2018